2016
DOI: 10.5430/afr.v5n3p107
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Information: Which Information Attracts Investors Attention First?

Abstract: This study extends Obaidat (2016) and Mohan & John (2011) studies by investigating the accounting information that is considered more value relevant for individual investors in Amman Stock Exchange (ASE), emphasizing earning and cash flows information. In addition, the study examined if investors have the time and abilities to assess the accounting information. Finally, this study measured the degree of consensus among different types of investors concerning the issues investigated. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This resonates with the findings in this study in general terms. Obaidat (2016) found that the most value relevant financial information is financial risk (among other accounting statement variables). This supports the findings in this research, where relative financial risk is value relevant.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This resonates with the findings in this study in general terms. Obaidat (2016) found that the most value relevant financial information is financial risk (among other accounting statement variables). This supports the findings in this research, where relative financial risk is value relevant.…”
Section: Discussion Of Findingsmentioning
confidence: 99%